Does bank liquidity creation contribute to economic growth? Evidence from Russia - Jarko Fidrmuc; Zuzana Fungáčová; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2015)
​The financial crisis has shown that the liquidity creation function of banks is critical for the economy. In this paper, we empirically investigate whether bank liquidity creation fosters economic growth in a large emerging market, Russia. We follow the methodology of Berger and Bouwman (2009) to measure bank liquidity creation using a rich and exhaustive dataset of Russian banks. We perform fixed effects and GMM estimations to examine the relation of liquidity creation to economic growth for Russian regions in the period 2004–2012. Our results suggest that bank liquidity creation fosters economic growth. This effect was not washed out by the financial crisis. Our conclusion thus supports a positive impact of financial development on economic growth in Russia.
URN:NBN:fi:bof-201503111110
Keywords: E44; G21; 330